The Potentials and Limits of Fandom-based Charitable Activism in Indonesia - Isnani Umi Muslikhah; M Falikul Isbah (SOSHUM : Jurnal Sosial dan Humaniora, 2022)
Fandom-based social movement, particularly charitable activism, has become increasingly widespread globally in today's digital era. The digital platform plays a massive role in the emergence of a new crowdfunding trend. This study aims to examine the potential and limitations of fandom-based charitable activism in Indonesia and to what extent this activism plays a role in empowering marginalized communities. This research employed a qualitative approach based on secondary data collected from several sources. This article finds that high loyalty and solidity positively correlate with the level of fan involvement in contributing to charitable activities. The youth's dominance and attachment to technology and social media potentially make this movement a broader and long-term impact. However, these activities tend to be sporadic and have not yet addressed the specific issues of marginalized communities. Also, the dependence of fans on the existence of their idols is a challenge for this movement.